Etika Sosial dalam Tafsir Al-Qur'an sebagai Landasan Mewujudkan Masyarakat Inklusif di Indonesia Menghadapi Era Society 5.0 - Zaini, Ahmad; Samsul Ma’arif, Moh.; Fawaid Jufri, Muhammad; Asizah, Siti (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study aims to examine the relevance of social ethics values in Qur'anic exegesis (tafsir) as a foundation for realizing an inclusive society in Indonesia facing the Society 5.0 era, with a focus on the challenge of digital inequality. Employing a qualitative approach with the thematic interpretation method (al-tafsir al-maudhu'i), this research analyzes verses on social ethics from classical, contemporary, and Nusantara tafsir works, while also examining empirical data on digital inequality among informal workers in Maluku Province. The findings reveal that the values of 'adl (justice), rahmah (compassion), musāwah (equality), and the prohibitions of fahsya (abomination) and munkar (evil) possess fundamental relevance in responding to digital inequality experienced by informal workers in rural areas, the primary sector, older generations, and those with low education levels. The integration of these values produces an ethical framework demanding digital transformation policies that favor vulnerable groups through infrastructure equalization, targeted digital literacy programs, and ethical artificial intelligence governance. This research contributes to the development of contextual tafsir studies and the formulation of equitable digital transformation policies in Indonesia.